Muscle invasive bladder cancer treated with gemcitabine plus cisplatin as neoadjuvant chemotherapy during the second trimester of pregnancy - Takeshi Sasaki; Ikadai Ryota; Akinobu Ishiyama; Sho Takakura; Momoko Kato; Shunsuke Owa; Taketomo Nishikawa; Shinichiro Higashi; Kouhei Nishikawa; Takahiro Inoue (IJU Case Reports)
Introduction Muscle invasive bladder cancer during pregnancy is scarcely reported. Case presentation A 41‐year‐old ex‐smoker Asian female, managed with clean intermittent catheterization for 3 years due to neurogenic bladder caused by spinal cord disease, presented with gross hematuria at 10 weeks of gestation. The patient was diagnosed with muscle invasive bladder cancer, cT3aN0M0. Maternal treatment was prioritized and gemcitabine plus cisplatin as neoadjuvant chemotherapy was started at 17 weeks of gestation. Cesarean section was performed at 32 weeks of gestation, followed by robot‐assisted radical cystectomy 3 weeks later. Histopathological examination revealed urothelial carcinoma, G3, ypT3b. Postoperative adjuvant nivolumab followed by enfortumab vedotin was not successful and the patient died 8 months after robot‐assisted radical cystectomy. Unfortunately, the premature infant with congenital heart disease died of necrotizing enterocolitis at 1‐month‐old. Conclusion Gemcitabine plus cisplatin chemotherapy in the patient with muscle invasive bladder cancer during pregnancy was safe but ultimately resulted in unfavorable outcomes in this case.